Aktualisasi Diri Untuk Mengembangkan Kompetensi Profesional Calon Konselor - David Ari Setyawan (STKIP Andi Matappa, 2020)
This study aims to determine the effectiveness of self-actualization of group guidance services to the professional competencies of student counselors majoring in Islamic Counseling Guidance at the Tulungagung State Islamic Institute. The research method uses quasi-experimental or pre-experimental research in the design and uses quantitative research in processing the data After being given group guidance services with self-actualization material for 7 times, it is necessary to increase professional mastery and professional counselors. 88-108 interval, the number of scores that can be agreed to mastering high professional counselor competence with 9 respondents' frequency answers with a percentage reaching 55.55% and the corresponding number of answer scores at 88-108 intervals reaching 41.67%. Group guidance service with self-actualization material turned out to be effective to improve professional competence with a calculated coefficient t = 11.25.